Adverbs of Mobility: Usage Challenges Among Kri University Students - Muhi, Zubair Hamad; Dajang, Innocent Nasuk (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2023)
An adverb is used to indicate roughly how frequently a typical or usual action or event occurs. It is one of the fundamental English grammar structures that present challenges for students at KRI University. The aim of this paper was to investigate the challenges of the mobility of adverbs among KRI University students. The instrument used for data collection was the open-ended questionnaire created via a Google Form with a five-item structure shared with participants. SPSS version 21 software was used to analyze the data, which was deployed at five universities in KRI at the upper secondary level to evaluate how effectively the respondents used adverbs. The results were examined using simple percentages. Many of the respondents were found to often place adverbs in ways that led to illegible and unclear sentences. Additionally, some students were found to misuse classes of words, using one when they should use the other. Since adverbs cannot just be used in every sentence positions, the study concluded that adverbs and adverbials genuinely display restricted mobility occurring in just three positions: initial, middle and final. Accordingly, the result of the study of adverb movement depends largely on the adverb's subtype and nature which have a significant role in determining its mobility.